Vibration with control - Inman, Daniel John (John Wiley & Sons, Inc., 2017)
An advanced look at vibration analysis with a focus on active vibration suppression As modern devices, from cell phones to airplanes, become lighter and more flexible, vibration suppression and analysis becomes more critical.